Circulating and deposited immune complexes in renal disease and their clinical correlation. Issue 11 (November 1979) - Cohen, S L; Fisher, C; Mowbray, J F; Hopp, A; Burton-Kee, J
Abstract : In 48 patients undergoing renal biopsy there was a strong correlation (chi 2 11.45 (P less than 0.01)) between the demonstration of circulating and deposited immune complexes. Serial studies of circulating immune complex levels have shown fluctuations which only sometimes appear to coincide with clinical changes in individual patients.